Die in europäischen Kiefernbuschhornblattwespen (Diprionidae) parasitierenden Ichneumonidae (Hymenoptera). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1966)
This taxonomic and nomenclatural study of European Ichneumonidae bred from Diprion cocoons is based on extensive material obtained by breeding and on the investigation of types. Almost all species are described in detail for the first time with regard to modern morphological characteristics, many new synonyms are established, and lectotypes are determined. Previous publications and the available material are critically assessed with the aim of compiling complete data about distribution, hosts, biology and development of these species. 36 species of Ichneumonidae can be regarded as primary parasites on Diprion, 11 are facultative or obligate hyperparasites, 9 are occasional parasites, while 48 species counted among parasites on Diprion in previous publications cannot be included in this complex of parasites. Data on identification, biology, economic importance and parasites of the 10 endemic host species are given in the first part of the study. - The keys of the hosts, their larvae and cocoons and the Ichneumonidae living on them as parasites will make identification possible also for non-specialists. Nomenclatural Actsfumipennis (Gravenhorst, 1829) (Agrothereutes), Lectotype; comb. n. hitherto Cryptus fumipennismandator (Linnaeus, 1758) (Agrothereutes), comb. n. hitherto Ichneumon mandatorpugnax (Hartig, 1838) (Aptesis), comb. n. hitherto Phygadeuon pugnaxretectus Hartig, 1838 (Campoplex), syn. n. of Olesicampe (Holocremnus) macellator (Thunberg, 1822)albolineatus Gravenhorst, 1829 (Cryptus), Lectotype now a synonym of Agrothereutes adustus (Gravenhorst, 1829)contractus Gravenhorst, 1829 (Cryptus), Lectotype now a synonym of Aptesis subguttatus (Gravenhorst, 1829)nubeculatus Gravenhorst, 1829 (Cryptus), Lectotype now a synonym of Agrothereutes adustus (Gravenhorst, 1829)pygoleucus Gravenhorst, 1829 (Cryptus), Lectotype now a synonym of Agrothereutes abbreviator (Fabricius, 1793)solitarius Tschek, 1870 (Cryptus), syn. n. of Agrothereutes fumipennis (Gravenhorst, 1829)erythrogaster (Gravenhorst, 1829) (Endasys), Lectotype hitherto Phygadeuon erythrogasteradspersus Hartig, 1838 (Exenterus), Lectotypeoriolus Hartig, 1838 (Exenterus), Lectotypenematorum Tschek, 1871 (Limneria), syn. n. of Olesicampe (Holocremnus) macellator (Thunberg, 1822)ratzeburgi Tschek, 1871 (Limneria), syn. n. of Olesicampe (Holocremnus) macellator (Thunberg, 1822)marginatus Brischke, 1871 (Mesoleius), syn. n. of Lamachus ophthalmicus (Holmgren, 1855)spectabilis Holmgren, 1876 (Mesoleius), syn. n. of Lamachus ophthalmicus (Holmgren, 1855)oblongopunctatus Hartig, 1838 (Paniscus), Lectotype now a synonym of Lophyroplectus luteator (Thunberg, 1822)probus Taschenberg, 1865 (Phygadeuon), Lectotype; syn. n. of Aptesis pugnax (Hartig, 1838)pteronum Hartig, 1838 (Phygadeuon), Lectotype now synonym of Pleolophus basizonus (Gravenhorst, 1829)texana Cresson, 1870 (Pimpla), syn. n. of Delomerista laevis (Gravenhorst, 1829)larvatus (Gravenhorst, 1829) (Pleolophus), comb. n. hitherto Phygadeuon larvatussericans (Gravenhorst, 1829) (Pleolophus), Lectotype; comb. n. hitherto Phygadeuon sericanslophyrum Hartig, 1838 (Tryphon), syn. n. of Lamachus frutetorum (Hartig, 1838)scutulata (Hartig, 1829) (Zemiophora), Lectotype described as Tryphon scutulatus